Tetragonal and cubic zirconia multilayered ceramics: investigation of electrical parameters during automated EPD processing. (January 2014) - Fleckenstein, C.; Mochales, C.; Frank, S.; Kochbeck, F.; Zehbe, R.; Fleck, C.; Mueller, W-D.
<x content-type="archive" xml:space="preserve">Abstract</x> The interest in electrophoretic deposition (EPD) of ceramics has widely increased owing to its versatility to combine different materials in unique shapes and structures interesting for several applications (e.g. solid oxide fuel cells, thermal barrier coatings and biomaterials). In this work, an automated robotic EPD set-up was constructed and used to produce tetragonal and cubic zirconia multilayered specimens, which combine the high conductivity of the cubic layer with the high toughness of the tetragonal layer. This automated EPD set-up allowed us to study in detail the very sensitive EPD process, whose success highly depends on a good control of the EPD parameters (e.g. electrode distance, applied tension, deposition time). Tetragonal layers of 20 μm and cubic layers of 10 μm were obtained with high reproducibility. The in situ measurement of the electric current evolution with the deposition time enabled us to analyse the EPD process for each layer.